TAX DEDUCTIBLE SEBAGAI KOMPENSASI KEGIATAN SOCIAL RESPONSIBILITY LEMBAGA NOTARIS DALAM PENGESAHAN BADAN HUKUM YAYASAN PONDOK PESANTREN - PUTRI ECHATARINA; MARTIN ROESTAMY (Magister Hukum Sekolah Pascasarjana Unida, 2018)
The Foundation is a body that perform various non commercial activities (non-profit) and engaged in social, religious or educational one boarding school. Boarding School can be said to have a role as well as educate the nation's children because schools have a main function of the students can study and master the knowledge of Islam more deeply. Identification of this research are: 1) How is social responsibility in implementing the notary profession and professional public service to educational institutions and religious boarding school? 2) How is the implementation of income tax from the practice of social responsibility in relation to the obligation to pay income tax on any notary deed? 3) Are there policies about tax deductible to the practice of social responsibility that does not charge the notary deed or honorarium from clients who set up a foundation online boarding school?. The method used in this research is normative juridical approach, the law conceived as norms, rules, principles or dogmas/jurisprudence.